As interconexões entre a gestão da informação e a gestão do conhecimento para o gerenciamento dos fluxos informacionais - Santos, Cássia Dias [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (My University, 2014)
Discusses the interconnections between information management and knowledge management for themanaging of information flows. Starting at a literature review to obtain a grounding that allows clarifythis question. Presents the peculiarities involving the formal flows management [informationmanagement] and informal flows management [knowledge management], as well as factors thatprovide a better understanding in regard to the focus of information management and knowledgemanagement. The efficient information flows management demands the need to deploy the informationand knowledge management to its true effectiveness. We can see that these two modes of managementare interrelated such that, in the absence of a, the other is affected, directly impacting the informationflows management and thus in the organization capacity to create knowledge and make decisions withcompetitive differential.

Aborda as interconexões entre a gestão da informação e a gestão do conhecimento para o gerenciamento dos fluxos informacionais. A partir de uma revisão de literatura de modo a obter um embasamento que permita aclarar essa questão. Apresenta as peculiaridades que envolvem a gestão dos fluxos formais [gestão da informação] e dos fluxos informais [gestão do conhecimento], bem como os fatores que propiciam uma melhor compreensão no que tange ao foco da gestão da informação e da gestão do conhecimento. O gerenciamento eficiente dos fluxos informacionais demanda a necessidade de se implantar a gestão da informação e do conhecimento para sua real efetividade. Evidencia-se que esses dois modos de gestão se inter-relacionam de tal forma que, na ausência de uma a outra é afetada, repercutindo diretamente na gestão dos fluxos de informação e, assim, na capacidade de a organização gerar conhecimento e tomar decisões com diferencial competitivo.
The Interconnections between information management and knowledge management for managing informations flows
Keywords: Fluxos de Informação; Fluxos Informacionais; Gestão da Informação; Gestão do Conhecimento; Ambientes Organizacionais; Interconexões